2015
DOI: 10.1016/j.meegid.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Maternal human leukocyte antigen-G (HLA-G) genetic variants associate with in utero mother-to-child transmission of HIV-1 in Black South Africans

Abstract: A 14-bp insertion/deletion (indel) within the 3' untranslated region (3’UTR) that affects HLA-G expression has been associated with HIV-1 mother-to-child transmission (MTCT). However, other 3’UTR single nucleotide polymorphisms (SNPs) that influence HLA-G mRNA stability have been described but not analyzed in the context of MTCT, and little is known about the role of HLA-G alleles. We examined HLA-G alleles and 3’UTR SNPs, including the 14-bp indel, in 216 mother-infant pairs from Johannesburg, South Africa. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 52 publications
0
12
1
Order By: Relevance
“…When analysing the role of HLA-G in the vertical (mother to child) transmission (Hong et al, 2015), it was found that the HLA-G allele, G( * )01:01:02 (in strong linkage disequilibrium with the 14-bp insertion) and +3187G SNP were significantly overrepresented in transmitters mothers compared to nontransmitter mothers, suggesting that polymorphisms of this gene may be relevant in this maternal transmission. Table 2 shows some viral infections associated with HLA-G.…”
Section: Chronic Viral Infectionsmentioning
confidence: 99%
“…When analysing the role of HLA-G in the vertical (mother to child) transmission (Hong et al, 2015), it was found that the HLA-G allele, G( * )01:01:02 (in strong linkage disequilibrium with the 14-bp insertion) and +3187G SNP were significantly overrepresented in transmitters mothers compared to nontransmitter mothers, suggesting that polymorphisms of this gene may be relevant in this maternal transmission. Table 2 shows some viral infections associated with HLA-G.…”
Section: Chronic Viral Infectionsmentioning
confidence: 99%
“…In vitro , transfection of the 14-bp ins/ins HLA-G into K562 cells resulted in increased levels of membrane-bound HLA-G1 expression with higher mRNA stability and lower sHLA-G1 ratio ( 257 ). However, studies on the impact of the 14-bp insertion on HIV-1 vertical transmission risk report conflicting results ( 258 260 ). In horizontal transmission, the frequency of the 14-bp ins/ins genotype was enriched in HIV-1–infected patients in African (but not European) subjects ( 261 ).…”
Section: Introductionmentioning
confidence: 99%
“…SNP 3206 (rs9380142) has been previously associated with HIV infection [65]. In our study, the AA genotype distribution was significantly different between HIV-uninfected and infected PE groups.…”
Section: Discussionmentioning
confidence: 42%